Technology-Based Financial Risk Management Strategy: Overview of Recent Developments - Budi Utami; Wahyu Widjayanti; Kartika Sukmawati; Mulatsih (Global Writing Academica Researching & Publishing, 2023)
Technological developments have had a significant impact on financial risk management. In this context, the application of artificial intelligence, the use of data analytics, and the role of blockchain technology are the main focus for increasing efficiency and accuracy in managing financial risks. This study aims to analyze technology-based financial risk management strategies with a focus on the application of artificial intelligence, the use of data analytics, and the role of blockchain technology. This research was conducted using a qualitative approach with a literature study as a research method. The data used comes from the results of previous research and studies that are related to technology-based financial risk management. This study found that technology-based financial risk management provides advantages in the form of operational efficiency, cost savings, and increased accuracy in risk analysis. However, challenges such as data security and privacy and the complexity of technology system integration must be overcome. In developing an effective technology-based risk management strategy, companies need to increase organizational understanding and awareness, develop a supportive regulatory framework, and conduct human resource skills training. Collaboration, continuous evaluation, and a sustainable approach are also keys to success in optimizing the use of technology in managing financial risks.